BENIGN PATHOLOGY AND ADVANTAGES OF LAPAROSCOPY IN UROLOGICAL SURGERY - Ahmad Farooq; Mohammad Mujtaba Khokhar (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Laparoscopy, often known as keyhole surgery, involves performing surgical procedures through small incisions (0.5 to 1.5 cm) using miniature telescopic equipment. A laparoscope, equipped with a camera and lenses, facilitates this minimally invasive approach. Methods: A comprehensive literature review was conducted using Medline and Lilacs databases to assess the efficacy of laparoscopy in urological surgery for benign pathologies. Results: Compared to traditional open surgery, laparoscopy offers numerous advantages in urological procedures, including reduced bleeding, lower operative morbidity, shorter hospital stays, decreased post-operative pain, improved aesthetic outcomes, and faster recovery. Conclusion: Qualitative analysis supports the conclusion that laparoscopy is highly effective in urological surgery for benign conditions, providing significant benefits such as reduced bleeding and quicker recovery times. Notably, data suggests decreased transfusion requirements among Jehovah’s Witnesses.